Nurse perceptions of practice environment, quality of care and patient safety across four hospital levels within the public health sector of South Africa - Immaculate Sabelile Tenza; Alwiena J. Blignaut; Suria M. Ellis; Siedine K. Coetzee (BMC, 2024)
Abstract Improving the practice environment, quality of care and patient safety are global health priorities. In South Africa, quality of care and patient safety are among the top goals of the National Department of Health; nevertheless, empirical data regarding the condition of the nursing practice environment, quality of care and patient safety in public hospitals is lacking. Aim This study examined nurses' perceptions of the practice environment, quality of care and patient safety across four hospital levels (central, tertiary, provincial and district) within the public health sector of South Africa. Methods This was a cross-sectional survey design. We used multi-phase sampling to recruit all categories of nursing staff from central (n = 408), tertiary (n = 254), provincial (n = 401) and district (n = 244 [large n = 81; medium n = 83 and small n = 80]) public hospitals in all nine provinces of South Africa. After ethical approval, a self-reported questionnaire with subscales on the practice environment, quality of care and patient safety was administered. Data was collected from April 2021 to June 2022, with a response rate of 43.1%. ANOVA type Hierarchical Linear Modelling (HLM) was used to present the differences in nurses' perceptions across four hospital levels. Results Nurses rated the overall practice environment as poor (M = 2.46; SD = 0.65), especially with regard to the subscales of nurse participation in hospital affairs (M = 2.22; SD = 0.76), staffing and resource adequacy (M = 2.23; SD = 0.80), and nurse leadership, management, and support of nurses (M = 2.39; SD = 0.81). One-fifth (19.59%; n = 248) of nurses rated the overall grade of patient safety in their units as poor or failing, and more than one third (38.45%; n = 486) reported that the quality of care delivered to patient was fair or poor. Statistical and practical significant results indicated that central hospitals most often presented more positive perceptions of the practice environment, quality of care and patient safety, while small district hospitals often presented the most negative. The practice environment was most highly correlated with quality of care and patient safety outcomes. Conclusion There is a need to strengthen compliance with existing policies that enhance quality of care and patient safety. This includes the need to create positive practice environments in all public hospitals, but with an increased focus on smaller hospital settings.